Endometrial Histology in Abnormal Uterine Bleeding with Risk Factors - Rudy Hasan; Eddy Suparman; Rudy A Lengkong (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To determine the endometrial histology in abnormal uterine bleeding (AUB) patients with risk factors. Method: This study involved 30 patients with complaints of AUB, aged over 35 years with associated risk factors of parity, obesity and fasting blood glucose in the outpatient clinic at Prof. Dr. R. D. Kandou General Hospital Manado, from July 2013 until October 2013. Patients who agreed to be involved in this study, underwent dilatation and curettage (D&C) to assess the endometrial histology that was grouped as the hyperplasia and non-hyperplasia groups. Result: From the results of the study, 7 patients were in the 35-40 years age group (23.3%) and in the 41-50 years age group were 23 patients (76.7%). Based on parity, 11 patients (36.7%) were nulliparous and 19 patients (63.3%) were multiparous. Based on the BMI, 16 patients (53.5%) were obese and 14 patients (46.7%) were non-obese. And based on the results of fasting blood sugar, similar results was obtained in normal and abnormal fasting blood glucose with the results of 15 patients in each groups (50%). And from all of patients who underwent D&C, endometrial hyperplasia was shown in 21 patients (70%) and non-hyperplasia endometrium in 9 patients (30%). From the results of Fischer exact test, a significantly high association was obtained between BMI and fasting blood glucose with the occurrence of endometrial hyperplasia. Conclusion: There is a significant relationship between BMI and high fasting blood glucose with endometrial hyperplasia. [Indones J Obstet Gynecol 2015; 3: 146-150] Keywords: age, AUB, BMI, endometrial hyperplasia, fasting blood sugar, parity